Social Campaign Signs in Ruteng, Flores Eastern Indonesia (A Case Study on Jendral Ahmad Yani Street) - Gabriel Fredi Daar; I Nyoman Suparwa; Anak Agung Putu Putra (Pusat Kegiatan Belajar Masyarakat (PKBM) Sambi Poleng, 2023)
Outdoor sign of social campaign is needed to increase awareness and knowledge of the viewer and foster positive perceptions and behaviours. Social campaigns signs can be made by the government or private parties concerned about human living and usually placed in public places. This study aims to analyse social campaign outdoor signs’ verbal and visual grammar. The data were collected through photographic techniques by documenting the outdoor signs using a digital camera. The data were obtained from social campaign outdoor signs placed in the street of Jenderal Ahmad Yani as one of the main streets in Ruteng, Flores, Indonesia. The results showed that the government provides the outdoor signs of a social campaign to change people’s behaviour. The outdoor signs use local language in verbal signs. It represents an effort to facilitate the viewer to obtain the meaning of information given by the sign easily. It is also found that the social campaign outdoor signs use social language that tends to be more formal, and verbal signs are used dominantly. They are placed at the centre of the sign and are the most salient elements. However, other participants are as salient as the main element and are considered to reduce the viewer’s attention to focus more on the main element of the sign. Thus, it is recommended that the next study focuses on analysing the producer (government) motive to use more verbal signs in social campaign outdoor signs in Jenderal Ahmad Yani Street in Ruteng, Indonesia.